2019
DOI: 10.1017/s0950268819001894
|View full text |Cite
|
Sign up to set email alerts
|

Persistent socioeconomic and racial and ethnic disparities in pathogen burden in the United States, 1999–2014

Abstract: The disproportionate burden of prevalent, persistent pathogens among disadvantaged groups may contribute to socioeconomic and racial/ethnic disparities in long-term health. We assessed if the social patterning of pathogen burden changed over 16 years in a U.S.-representative sample. Data came from 17 660 National Health and Nutrition Examination Survey participants. Pathogen burden was quantified by summing the number of positive serologies for cytomegalovirus, herpes simplex virus-1, HSV-2, human papillomavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The ensuing background level of multiple layers of immune manipulation have been linked to chronic mental and physical diseases including autoimmunity [ 33 , 34 , 35 , 36 , 37 ], increased speed of ageing [ 38 , 39 , 40 , 41 ], and chronic inflammation [ 42 ]. Pathogen burden is highest among the most disadvantaged social groups [ 43 ]—who also experience lower lifespan.…”
Section: A Wider Context To Pathogen Interferencementioning
confidence: 99%
“…The ensuing background level of multiple layers of immune manipulation have been linked to chronic mental and physical diseases including autoimmunity [ 33 , 34 , 35 , 36 , 37 ], increased speed of ageing [ 38 , 39 , 40 , 41 ], and chronic inflammation [ 42 ]. Pathogen burden is highest among the most disadvantaged social groups [ 43 ]—who also experience lower lifespan.…”
Section: A Wider Context To Pathogen Interferencementioning
confidence: 99%
“…For example, mice latently infected with herpesviruses were found to be resistant to infection with Listeria monocytogenes and Yersinia pestis ( 115 ). A recent study in the United States found higher rates of seropositivity for HSV-1, HSV-2, and CMV in people of lower SES ( 116 ), but it is not clear that the putative immunostimulatory effects overcome the other disadvantages of these infections or of low SES.…”
Section: Evolution and Necessary Microbial Exposuresmentioning
confidence: 99%
“…Data from the United States show that socioeconomic status is a strong predictor of latent infection with CMV and other herpesviruses [ 43 ].…”
Section: CMVmentioning
confidence: 99%